If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -3 = -2x + 25 Reorder the terms: -3 + 5x = -2x + 25 Reorder the terms: -3 + 5x = 25 + -2x Solving -3 + 5x = 25 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -3 + 5x + 2x = 25 + -2x + 2x Combine like terms: 5x + 2x = 7x -3 + 7x = 25 + -2x + 2x Combine like terms: -2x + 2x = 0 -3 + 7x = 25 + 0 -3 + 7x = 25 Add '3' to each side of the equation. -3 + 3 + 7x = 25 + 3 Combine like terms: -3 + 3 = 0 0 + 7x = 25 + 3 7x = 25 + 3 Combine like terms: 25 + 3 = 28 7x = 28 Divide each side by '7'. x = 4 Simplifying x = 4
| 100-5x=4x-71 | | -7w+4(w+4)=28 | | 1=v/-2 | | 100=4(3.14)r^2 | | k/4=3/4 | | y−2=3/4(x−1) | | h/4=4 | | X^2+2x-48=24 | | 2tanx=6 | | 9x^2+25+36x^2+81=0 | | 3x+7=4x+12 | | 6(4n)=90 | | x-6+3x=100-10x-50 | | -5=p+-20 | | -3b=3 | | 8x+5x-7x= | | (1)/(16))^(-n)*16^(n)=6^(1-2n) | | X^2-450=300 | | F(x)=-6x^2-6x+12 | | (3x+24)=(x+36) | | 1-x^2m=0 | | 0.5x-6=3 | | 1-mx^2=0 | | (2x-13)=97 | | 13-(x-9)=15 | | ln(x+7)+2=0 | | 14278.9227=1/3*1267.36 | | 40=17+x | | 5x+8i=3xi+2 | | 7x-4=8x-3 | | 4(x-7)=90 | | (5x-44)=(2x) |